Oral history interview with Lawrence Welke - Welke, Lawrence (Charles Babbage Institute, 2002)
Lawrence Welke played a critical role in helping to define and advance the early software industry through publishing ICP (International Computer Programs) Quarterly, a subscription-driven catalog of software products that soon evolved into an advertising-driven software directory. Welke discusses his early work at IBM and in the banking industry, and how these experiences led him to form ICP. He reflects on advertising and marketing in the early software services and products industries, and the evolution of these trades in the mini and microcomputing eras. He also details the growth of ADAPSO and its significance to the software industry’s development. He concludes with remarks on societal impacts and the future potential of computing technology. This oral history was sponsored by the Software History Center in conjunction with the Center's ADAPSO reunion (3 May 2002).
Transcript, 24 pp.
Keywords: Computer history; ADAPSO.; Computer software -- Marketing; I.C.P. quarterly.; International Business Machines Corporation.